Herpes Simplex Encephalitis - Goel U. C; Singh K. G; Rajpur Vandana (Wolters Kluwer Medknow Publications, 1999)
A twenty five year old female patient presented with bilateral grouped vesicular lesions with altered sensorium. It was diagnosed as herpes simplex encephalitis (type II)